2016
DOI: 10.1186/s12886-016-0394-y
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative occlusion of visual axis with fibrous membrane in the presence of anterior capsular phimosis in a patient with pseudoexfoliation syndrome: a case report

Abstract: BackgroundTo report a case of postoperative fibrous membrane formation occluding the visual axis in the presence of anterior capsular phimosis in a patient with pseudoexfoliation syndrome.Case presentationA 79-year-old Asian woman with pseudoexfoliation syndrome underwent uneventful phacoemulsification and implantation of one-piece hydrophilic acrylic square-edged intraocular lens (Cristalens) in the right eye. Two months later, she had blurred vision in the right eye with the best-corrected visual acuity (BCV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…As for mechanical studies, it has been indicated that the decrease or enlargement of the capsulorhexis area is associated with the resultant centrifugal force from the contraction of normal lens fibers and the resultant centripetal force from the contraction of lens fibers at the edge of the capsulorhexis area ( 13 , 14 ). Therefore, ACCS occurs in patients with weaken zonules because of the imbalance between the centrifugal force generated by the contraction of zonules and the centripetal force generated by the contraction of lens fibers at the edge of the capsulorhexis area.…”
Section: Pathogenesis Of Accsmentioning
confidence: 99%
“…As for mechanical studies, it has been indicated that the decrease or enlargement of the capsulorhexis area is associated with the resultant centrifugal force from the contraction of normal lens fibers and the resultant centripetal force from the contraction of lens fibers at the edge of the capsulorhexis area ( 13 , 14 ). Therefore, ACCS occurs in patients with weaken zonules because of the imbalance between the centrifugal force generated by the contraction of zonules and the centripetal force generated by the contraction of lens fibers at the edge of the capsulorhexis area.…”
Section: Pathogenesis Of Accsmentioning
confidence: 99%
“…ACCS is characterized by an excessive fibrosis response after capsulorhexis, which causes reduction in the size of the anterior capsulotomy and capsular bag diameter. It is often associated with impairment of visual function [3][4][5][6][7][8]. Rarely, this zonular traction may lead to IOL dislocation and retinal detachment [1,9].…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 3 Opacification and severe contraction of the anterior capsule can cause a reduction in visual quality, as well as intraocular lens (IOL) decentration and/or tilt. 4 6 In extreme cases, zonular traction may lead to IOL dislocation and retinal detachment. 7 …”
Section: Introductionmentioning
confidence: 99%
“…1,3 Opacification and severe contraction of the anterior capsule can cause a reduction in visual quality, as well as intraocular lens (IOL) decentration and/or tilt. [4][5][6] In extreme cases, zonular traction may lead to IOL dislocation and retinal detachment. 7 Since Davison first advocated the use of neodymium:YAG (Nd:YAG) laser anterior capsulotomy for disrupting the contraction forces without further surgical intervention, Nd:YAG laser radial anterior capsulotomies have typically been performed to enlarge the opening area when capsular phimosis develops.…”
Section: Introductionmentioning
confidence: 99%